Cell non-autonomous effect of hepatic growth differentiation factor 15 on the thyroid gland - Jeong, Seonhyang; Lee, Seul Gi; Kim, Kook Hwan; Zhu, Xuguang; Lee, Woo Kyung; Lee, Hwa Young; Park, Sunmi; Lee, Myung-Shik; Cheng, Sheue-Yann; Lee, Jandee; Jo, Young Suk (Frontiers in Endocrinology, 2022)
The thyroid gland plays an essential role in the regulation of body energy expenditure to maintain metabolic homeostasis. However, to date, there are no studies investigating the morphological and functional changes of the thyroid gland due to mitochondrial stress in metabolic organs such as the liver. We used data from the Genotype-Tissue Expression portal to investigate RNA expression patterns of the thyroid gland according to the expression of growth differentiation factor 15 (GDF15) such as the muscles and liver. To verify the effect of hepatic GDF15 on the thyroid gland, we compared the morphological findings of the thyroid gland from liver-specific GDF15 transgenic mice to that of wild type mice. High GDF15 expression in the muscles and liver was associated with the upregulation of genes related to hypoxia, inflammation (TGF-α via NFκB), apoptosis, and p53 pathway in thyroid glands. In addition, high hepatic GDF15 was related to epithelial mesenchymal transition and mTORC1 signaling. Electron microscopy for liver-specific GDF15 transgenic mice revealed short mitochondrial cristae length and small mitochondrial area, indicating reduced mitochondrial function. However, serum thyroid stimulating hormone (TSH) level was not significantly different. In our human cohort, those with a high serum GDF15 level showed high fasting glucose, alanine transaminase, and alkaline phosphatase but no difference in TSH, similar to the data from our mice model. Additionally, high serum GDF15 increased the risk of lymph node metastasis to lateral neck. The hepatic GDF15 affected thyroid morphogenesis via a TSH-independent mechanism, affecting aggressive features of thyroid cancers.